Stereochemical course of hydrolytic reaction catalyzed by alpha-galactosidase from cold adaptable marine bacterium of genus Pseudoalteromonas - Bakunina, Irina Y.; Balabanova, Larissa A.; Golotin, Vasiliy A.; Slepchenko, Lyubov V.; Isakov, Vladimir V.; Rasskazov, Valeriy A. (Frontiers in Chemistry, 2014)
The recombinant α-galactosidase of the marine bacterium (α-PsGal) was synthesized with the use of the plasmid 40Gal, consisting of plasmid pET-40b (+) (Novagen) and the gene corresponding to the open reading frame of the mature α-galactosidase of marine bacterium Pseudoalteromonas sp. KMM 701, transformed into the E. coli Rosetta(DE3) cells. In order to understand the mechanism of action, the stereochemistry of hydrolysis of 4-nitrophenyl α-D-galactopyranoside (4-NPGP) by α-PsGal was measured by 1H NMR spectroscopy. The kinetics of formation of α- and β-anomer of galactose showed that α-anomer initially formed and accumulated, and then an appreciable amount of β-anomer appeared as a result of mutarotation. The data clearly show that the enzymatic hydrolysis of 4-NPGP proceeds with the retention of anomeric configuration, probably, due to a double displacement mechanism of reaction.